Interactive folklore - re-modernizing the culture through digital storytelling - Mohamad Nizam, Muhammad Ilham Hakimi; Mohd Fauzi, Fahd; Zainal Azmi, Nurazlin (IIUM Press, 2023)
This project focuses on developing an interactive visual novel prototype based on a popular Malaysian folklore, Batu Belah Batu Bertangkup. The aim is to modernize and digitize folklore as an interactive visual novel with branching narratives for teaching children about moral values through the story. This visual novel includes user interaction, core gameplay mechanics, storyline, character design, and backgrounds. The game is developed using Ren’Py for Windows PC as the platform